Efficacy of accelerated vaccination against Hbv to achieve antibody formation in multiple sclerosis patients receiving anti-Cd20 therapy - Emine Rabia Koc; Omer Faruk Turan; Furkan Saridas; Bedirhan Menguc; Sema Nur Minaz; Guven Ozkaya (Annals of Indian Academy of Neurology, 2023)
Aim: Ocrelizumab is a monoclonal antibody that has been approved for use in both relapsing–remitting multiple sclerosis (RRMS) and primary progressive multiple sclerosis (PPMS). Since ocrelizumab acts on B cells, it also affects humoral immunity, thus reducing the vaccine response. In this study, we aimed to elucidate the relationship between the antibody response following rapid vaccination against hepatitis B virus (HBV) in multiple sclerosis (MS) patients receiving ocrelizumab treatment, and the time of vaccination. Materials and Methods: A total of 220 MS patients were included in this retrospective analysis. The patients' baseline HBV serostatuses (HbsAg, Anti-HbsAb, Anti-HbcAb), previous drug history for MS, whether they were vaccinated against HBV in the past, vaccination status before or after ocrelizumab treatment, and protective antibody titers according to vaccination times, occult HBV incidence and initiation of antiviral treatment were evaluated. Results: Forty-nine percent of MS patients using ocrelizumab were not vaccinated against HBV. The patients were divided into three groups according to their vaccination status as: individuals vaccinated in the past (7.3%, n = 16), vaccinated before treatment (4.5%, n = 10), and vaccinated after treatment (22.3%, n = 49). The antibody titers of the patients in the 6th month after ocrelizumab treatment were measured as 78 mIU/ml, 193 mIU/ml, and 0, respectively. The number of patients with occult HBV infection was 38. Conclusion: In patients with a suspected diagnosis of MS, HBV serostatus should be evaluated at the beginning and if necessary, patients should be vaccinated in the early period. Vaccinating patients at least 1 month before initiating multiple sclerosis treatment is more effective in terms of protective antibody formation.